Identifying winning strategies: analysis of play-types in professional European basketball leagues - Alonso-Pérez-Chao, E.; Salazar, H.; Bustamante-Sánchez, Á.; Sansone, P.; Lorenzo, A. (International Journal of Performance Analysis in Sport, 2025)
This study analysed the utilisation and effectiveness of different play-types in elite European basketball. Additionally, it attempted to understand how team ability influences the use and efficacy of these play-types. Play-types data were collected from 6 European elite leagues, for a total of 11,189 games analysed. Information on the frequency of usage and efficiency of different play-types were extracted. A two-step cluster analysis was performed to differentiate high-performing (HP) and low-performing (LP) European basketball teams based on their winning percentage. A Mann-Whitney test was used to compare the effect of the team ability across play-types and their efficiency. HP teams used more catch-and-shoot, post-up and cutting actions (p < 0.05, effect size [ES] > 0.107), while LP teams used more pick-and-rolls (p < 0.05, ES = 0.132). Noticeably, better teams had higher efficiency (p < 0.05, ES > 0.124) on most play-types (including pick-and-roll, isolation, transition, and screen off), except for hand-off actions, which were similar in HP and LP. Teams with different abilities implement different offensive tactical plays, while better teams have greater efficiency on almost all offensive play-types compared to lower-performing teams. Current findings should be considered to develop effective training strategies and game plans which can optimise chances of success.